Changing conditions, persistent mentality: An anatomy of East German unhappiness, 1990-2016 - Philipp Biermann; Heinz Welsch (University of Oldenburg, Department of Economics, 2019)
We decompose the persistent satisfaction gap between East and West Germany into effects of objective circumstances and subjective mentality, the latter presumed to be a legacy of communist socialization. Using the methodology proposed by Senik (2014) in a cross-national context, we capture circumstances by the region of residence (East vs. West) and mentality by whether an individual is a "native" of the respective region or has moved ("migrated") to that region. We differentiate our analysis by years since German unification, birth cohorts, and the length of time a "migrant" has lived in her current region of residence. Using about 420,000 observations, 1990-2016, we find 54.4 percent of the satisfaction gap to be attributable to mentality. The mentality gap in the overall sample is driven by birth cohorts socialized under communism, the contribution of mentality to the satisfaction gap being 81.2 percent in this cohort group. While the circumstance-related gap diminished steadily over time, the mentality-related gap changed non-monotonically, reflecting different happiness responses of East and West Germans to politico-economic shocks. Exploiting the panel nature of our data, we find the mentality-related gap to show little indication of within-person changes over time.
Keywords: I31; P36; P16; D63; 330; Germany; happiness; life satisfaction; unification; mentality; communism